Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
6)
-2 x = 0 ⇒ -2 · 0 = 0 Prawda
5y + 5 = 5 ⇒ 5 · 0 + 5 = 5 ⇒ 5 = 5 Prawda
2z - 7 = 7 ⇒ 2 · 0 - 7 = 7 ⇒ -7 = 7 Nieprawda
7t + 9t = 0 ⇒ 7 · 0 + 9 · 0 = 0 ⇒ 0 + 0 = 0 Prawda
0 = 3 + 11d ⇒ 0 = 3 + 11 · 0 ⇒ 0 = 3 + 0 ⇒ 0 = 3 Nieprawda
7)
a) 2x + 1 = 9 - 2x ⇒ 2 · 2 + 1 = 9 - 2 · 2 ⇒ 4 + 1 = 9 - 4 ⇒ 5 = 5 Spełnia
b) 3(2x - 5) = 1 - 4x ⇒ 3 (2 · 1,5 - 5) = 1 - 4 · 1,5
⇒3 · (-2) = 1 - 6 ⇒ -6 = -5 Nie spełnia
c) 4(y - 6) - 3y = 2(y - 9) ⇒ 4 (-6 - 6) -3 · (-6) = 2 (-6 - 9)
⇒ 4 · (-12) + 18 = 2 · (-15) ⇒ - 48 + 18 = - 30 ⇒ - 30 = -30 Spełnia
I wszystko jasne
Pozdrawiam
[tex]zad.6\\\\a)\\-2x=0~~\mid \div (-2)\\\\x=0\\\\b)\\5y+5=5\\\\5y=5-5\\\\5y=0~~\mid \div 5\\\\x=0\\\\c)\\2z-7=7\\\\2z=7+7\\\\2z=14~~\mid \div 2\\\\z=7\\\\d)\\7t+9t=0\\\\16t=0~~\mid \div 16\\\\t=0\\\\e)\\0=3+11d\\\\-11d=3~~\mid \div (-11)\\\\d=-\dfrac{3}{11}[/tex]
Odp: Równania, których rozwiązaniem jest liczba zero to: -2x = 0 , 5y + 5 =5 oraz 7t + 9t = 0
[tex]zad.7\\\\a)~~2x+1=9-2x,~~x=2\\\\L=2\cdot 2 + 1=4+1=5\\\\P=9-2\cdot 2=9-4=5\\\\L=P~~\Rightarrow~~x=2~~spelnia~~rownanie\\\\b)~~3\cdot (2x-5)=1-4x,~~x=1\frac{1}{2}~~\Rightarrow~~x=\frac{3}{2} \\\\L=3\cdot (2\cdot \frac{3}{2} -5 )=3\cdot (3-5)=3\cdot (-2)=-6\\\\P=1-4\cdot \frac{3}{2}=1-6=-5\\\\L\neq P~~\Rightarrow~~x=1\frac{1}{2}~~nie~~spelnia~~rownania\\\\[/tex]
[tex]c)~~4\cdot (y-6)-3y=2\cdot (y-9),~~y=-6\\\\L=4\cdot (-6-6)-3\cdot (-6)=4\cdot (-12)+18=-48+18=-30\\\\P=2\cdot (-6-9)=2\cdot (-15)=-30\\\\L=P~~\Rightarrow~~y=-6~~spelnia~~rownanie[/tex]